Clinical teaching practices of nurse educators at a public college of nursing in South Africa: A survey study. (January 2021) - Gcawu, Sybil Nyameka; van Rooyen, Dalena (R.M.); Jordan, Portia; ten Ham-Baloyi, Wilma
Abstract: Standardisation of clinical teaching practices by nurse educators for undergraduate students is vital, especially within large nursing education institutions distributed over multiple campuses. This quantitative study investigated current clinical teaching practices of nurse educators at a Public College of Nursing in South Africa. A total of n = 68 nurse educators were selected from 5 campuses over a two-month period (April–May 2016), using convenience sampling. Data was collected with a structured questionnaire, the design of which was informed by the Dundee Three Circle Outcomes Model for Clinical Teaching. The results showed that 37% (n = 25) of the nurse educators had above 10 years of clinical teaching experience. Of the 66% (n = 45) who had formal education on clinical teaching practices, 49% (n = 33) received in-service education. Most nurse educators were willing to share amongst colleagues documents they used for clinical teaching, to promote standardisation of teaching practices. Further, they evidenced best clinical practices regarding planning for assessment and clinical placement of students. However, there were significant variations in the majority (seven) of the nine investigated clinical teaching practices among participants. In-service education was positively correlated to best clinical teaching practices (Chi square (d.f. = 2, n = 68) = 7.24; p = .027; V = 0.33 Medium). Highlights: This study investigated clinical teaching practices of South African nurse educators. Standardisation of clinical teaching practices does not always happen. Most nurse educators showed good clinical teaching practices. Variations were found in the clinical teaching practices of nurse educators. In-service training was positively correlated to best clinical teaching practices.